2015
DOI: 10.1093/brain/awv125
|View full text |Cite|
|
Sign up to set email alerts
|

The MDM4/MDM2-p53-IGF1 axis controls axonal regeneration, sprouting and functional recovery after CNS injury

Abstract: Regeneration of injured central nervous system axons is highly restricted, causing neurological impairment. To date, although the lack of intrinsic regenerative potential is well described, a key regulatory molecular mechanism for the enhancement of both axonal regrowth and functional recovery after central nervous system injury remains elusive. While ubiquitin ligases coordinate neuronal morphogenesis and connectivity during development as well as after axonal injury, their role specifically in axonal regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 58 publications
2
47
0
Order By: Relevance
“…They have observed that both MDMX deletion and MDM2 inhibition by nutlin‐3a enabled nerve regeneration after optic nerve crush or spinal cord injury . A genome‐wide gene expression analysis has indicated that IGF1R is a downstream effector of MDMX deletion, and the activity and expression of IGF1R are necessary for regeneration . These results suggest that the MDM2/MDMX‐p53‐IGF1 signaling axis contributes to axonal regrowth and functional recovery after CNS injury, and may be a promising target for improving axonal regeneration and neurological recovery.…”
Section: Roles Of Mdm2 In Other Noncancer Diseases and Conditionsmentioning
confidence: 98%
See 1 more Smart Citation
“…They have observed that both MDMX deletion and MDM2 inhibition by nutlin‐3a enabled nerve regeneration after optic nerve crush or spinal cord injury . A genome‐wide gene expression analysis has indicated that IGF1R is a downstream effector of MDMX deletion, and the activity and expression of IGF1R are necessary for regeneration . These results suggest that the MDM2/MDMX‐p53‐IGF1 signaling axis contributes to axonal regrowth and functional recovery after CNS injury, and may be a promising target for improving axonal regeneration and neurological recovery.…”
Section: Roles Of Mdm2 In Other Noncancer Diseases and Conditionsmentioning
confidence: 98%
“…Joshi et al have demonstrated that MDM2 and MDMX limit axonal regeneration in the central nervous system (CNS), particularly in the injured optic nerve, by regulating the p53‐insulin‐like growth factor 1 (p53‐IGF1) axis (Table ) . They have observed that both MDMX deletion and MDM2 inhibition by nutlin‐3a enabled nerve regeneration after optic nerve crush or spinal cord injury . A genome‐wide gene expression analysis has indicated that IGF1R is a downstream effector of MDMX deletion, and the activity and expression of IGF1R are necessary for regeneration .…”
Section: Roles Of Mdm2 In Other Noncancer Diseases and Conditionsmentioning
confidence: 99%
“…Accordingly, inhibition of the triad or one of its components promoted functional recovery after spinal cord injury. 67 …”
Section: The Role Of P53 In Nerve Regenerationmentioning
confidence: 99%
“…Additionally, GSK3β, whose downregulation stimulates axonal regeneration of sensory neurons 74 , inhibits the mTOR pathway by phosphorylating TSC2 in a manner dependent on AMPK-priming phosphorylation 73 . Interestingly, IGF1 signalling, recently shown to promote axonal regeneration by others and us 75,76 , is inhibited by AMPK activation 77 .…”
Section: Discussionmentioning
confidence: 96%